PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN ASINKRON BAGI DOSEN UNIVERSITAS SAMAWA - Ilfiani, Pratiwi Dian; Darmanto, Darmanto; Negara, Komang Metty Trisna; Haryadi, Wahyu (LPPM Institut Pendidikan Nusantara Global, 2022)
The Coronavirus, which was originally an obstacle in education, has now stimulated educators to do the innovation in the learning process. Learning with audio-visual media is an option for students to achieve better mastery. Audio-visual media enable the material can be delivered in the form of learning videos. A simple audio-visual media is Bandicam. This activity was held on Saturday, August 27, 2021, in the Engineering Faculty Meeting Hall, Samawa University, Sumbawa Besar. This activity was attended by lecturers from the Faculty of Engineering and the Faculty of Social and Political Sciences (FISIPOL) at Samawa University, Sumbawa Besar. This activity was divided into several sessions, namely the chairman report, elaboration of materials, and discussion. In general, the training was a success both in terms of the number of participants and the implementation. The training participants were very enthusiastic about gaining knowledge and experience regarding Bandicam. This training activity improves the ability of the trainees to operate and make learning videos using Bandicam.